2013
DOI: 10.1111/j.1556-4029.2012.02303.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological Estimation of Age at Death from the Compact Bone of Burned and Unburned Human Ribs

Abstract: This study describes the estimation of age at death from the compact bone of burned and unburned human ribs. Bone samples came from individuals of known age, sex, and cause of death. Each bone was divided into four sections; three sections were burned at 700, 800, and 1000°C. Undecalcified, unstained ground cross sections were photographed, and 28 variables were analyzed in the bones using SigmaScan Pro 5. Age-related as well as heat-induced microstructural changes were found. These changes were often very sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…The results obtained from using quantitative petrography in the analysis of burned bone compliment those ascertained by previous histological research (Absolonová et al, 2013; Castillo et al, 2013; Squires et al, 2011) and those derived from the examination of macroscopic colour (Ullinger & Sheridan, 2015). This is encouraging and, when teamed with the data from the interobserver study, shows that this method is reliable.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results obtained from using quantitative petrography in the analysis of burned bone compliment those ascertained by previous histological research (Absolonová et al, 2013; Castillo et al, 2013; Squires et al, 2011) and those derived from the examination of macroscopic colour (Ullinger & Sheridan, 2015). This is encouraging and, when teamed with the data from the interobserver study, shows that this method is reliable.…”
Section: Discussionsupporting
confidence: 87%
“…With regard to the preservation of histological microstructure, Brain (1993), Squires et al (2011) and Absolonová et al (2013) report that structures are still visible at 600°C. However, Hanson and Cain (2007) observed that histological structure disappeared between 482°C and 620°C.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, anthropologists have attempted to apply histomorphometry in age at death assessment, as quantitative methods such as histomorphometry are considered more objective by default, and clear and precise guidelines could ensure methodological reproducibility and repeatability. Also, some attempts have been made to analyse burned remains using histological methods (Absolonova et al 2012). Incinerated remains are extremely difficult to analyse due to extensive tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…For example, examiners have reported both an increase and decrease in osteon size as a result of an increase in temperature (Bradtmiller & Buikstra, 1984;Forbes, 1941;Hummel & Schutkowski, 1993;Nelson, 1992). In addition, the depletion of histological structure has also been described to occur at different temperatures (Absolonová, Veleminsky, Dobisikova, Beran, & Zocova, 2013;Brain, 1993;Hanson & Cain, 2007;Squires et al, 2011). These discrepancies have been attributed to a lack of standardisation in experimental design and sampling methods (Gonçalves, 2011).…”
Section: Histomorphology In Cremation Researchmentioning
confidence: 99%